« QAnon pastel » ou la surprenante convergence entre conspirationnisme politique et spiritualités New Age : Cyber-ethnographie d’activistes francophones - Farahmand, Manéli; Piraud, Mischa; Rouiller, Sybille (Anthropologica, 2023)
The QAnon discourse and New Age spiritualities are the subject of renewed connections. A qualitative study started in 2020 by the Intercantonal Information Center on Beliefs (CIC) in Geneva (Switzerland) presents, by means of a “cyber-ethnography,” a systematic analysis of over 60 online videos and interactive platforms disseminating QAnon discourses, between 2020 and 2023. The study highlights the specifics of the Swiss acceptance of QAnon views in the context of the pandemic (COVID-19) and the forms of hybridization that stem from this. Drawing on the concept of conspirituality, the article shows that, in the context of the COVID-19 crisis, QAnon theories, initially confined to the American political sphere, have expanded their audience well beyond the initial community. We thus observe a politicization of certain actors connected with the holistic environment and, in contrast, a watering down of QAnon theories within a millennial New Age-type narrative. This seemingly unexpected encounter between QAnon and the Swiss holistic-spiritual community is discussed along three axes : 1) the historic connection between parallel religiosities and the radical right ; 2) the radical individualistic turn within current New Age networks; and 3) the naturalist ideology characteristic of the holistic community.